WORKING ENVIRONMENT IMPACT ON THE LATVIAN LABOR MARKET GROWTH IN THE EDUCATION SECTOR - Silineviča, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Increasing participation of the elderly people in the labor market has significant potential to reduce the demographic burden. People who want to stay in the labor market longer and are physically fit to work longer should create the conditions for these opportunities. Research is needed to discover these options. Extending people's working lives depends on many factors. One of them is a working environment that is specific to each sector and different in each company. The aim of this research is to study the impact of some working environment factors on people's decision to work in retirement age in the education sector. This topic has not been sufficiently studied in Latvia yet. Express surveys and the survey methods were used for self-assessment of the impact of the working environment on people's decision to stay in the labor market longer. The developed proposals concern to creation of career support strategies for the elderly employeed. It will be able to promote the growth of labor market potential in Latvia in the education sector.